2017
DOI: 10.1177/1474515117715761
|View full text |Cite
|
Sign up to set email alerts
|

The association between supportive relatives and lower occurrence of anxiety and depression in heart patients: Results from a nationwide survey

Abstract: The presence of supportive relatives was found to be associated with lower occurrence of anxiety and depression. Health professionals should focus on including relatives in the treatment and rehabilitation of heart patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Very few studies concerning this topic (e.g. Cartledge et al., 2018; Hansen et al., 2017; Kähkönen, Kankkunen, Miettinen, Lamidi, & Saaranen, 2017; Köhler, Nilsson, Jaarsma, & Tingström, 2017) have been published in the last 3 years, which makes this article important and strengthens the novelty of it.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Very few studies concerning this topic (e.g. Cartledge et al., 2018; Hansen et al., 2017; Kähkönen, Kankkunen, Miettinen, Lamidi, & Saaranen, 2017; Köhler, Nilsson, Jaarsma, & Tingström, 2017) have been published in the last 3 years, which makes this article important and strengthens the novelty of it.…”
Section: Introductionmentioning
confidence: 85%
“…The most crucial thing is to define the concept of involvement because it can have many different meanings and manifestations. In this study, family involvement refers to how family members engage in the rehabilitation of a person diagnosed with coronary artery disease (CAD) and involvement is seen from two different viewpoints: family promoting rehabilitation and issues encumbering rehabilitation in family, which derive from the previous literature (Benyamini, Medalion, & Garfinkel, 2007; Cartledge, Feldman, Bray, Stub, & Finn, 2018; Dalteg, Benzein, Fridlund, & Malm, 2011; Hansen, Zinckernagel, Schneekloth, Zwisler, & Holmberg, 2017; Jackson, McKinstry, Gregory, & Amos, 2012; Kärner, Dahlgren, & Bergdahl, 2004; Mahrer‐Imhof, Hoffmann, & Froelicher, 2007; Rantanen et al., 2008; Wong et al., 2016). It has been shown that, in addition to spouses, children are special supporters for patients with CAD (Roos, Rantanen, & Koivula, 2012), but studies of the significance of other family members living in the same household are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Civil or cohabitation status is traditionally used as an indicator for practical and emotional support. 6,28,29 Our findings may contribute with additional information. Social support as a concept covers several dimensions and includes emotional, informational, instrumental and appraisal support, given not only by family members and spouses, but also by friends, neighbours and colleagues.…”
Section: Discussionmentioning
confidence: 58%
“…This was supported in another Danish study of supportive relatives of cardiac patients with anxiety and depression. 29 The authors found that having low or only some degree of support from relatives was associated with depression. Further, stratified by marital status, a stronger association was found between low or some degree of support and anxiety and depression for married patients compared with non-married or widowed.…”
Section: Discussionmentioning
confidence: 99%
“…This did not differ even when we took age, sex, diagnosis, place of residence, level of education, ethnicity, comorbidity and the working status of the patients into account. 1 Family and friends can make patients’ lives easier and therefore it may be a good idea to give your loved ones a thought at this joyful time. Why not pick up the phone and give them a call this year, send them a holiday card and perhaps even buy them that extra-large present for the holidays.…”
Section: Family and Friends Make Patients’ Lives Easier: A Reflectionmentioning
confidence: 99%